NT5E Mediates Cisplatin Resistance in NSCLC Through the PI3K-AKT Signaling Pathway - Liangfeng Zheng; Jian Liu; Feiyue Ji; Chunxiang Li; Ye Qian; Lili Shao; Xiaomin Lu (International Journal of Clinical Practice)
Conclusion: NT5E may be a key gene for DDP resistance in NSCLC cells, while its high expression may indicate a poor prognosis for patients. This finding provides important insights for a deeper understanding of the mechanism of drug resistance in lung cancer and serves as a theoretical basis for the development of new therapeutic strategies and drugs.